Financial Planning and Self-control on Retirement Well-being through Financial Behaviour: Evidence from a Developing Country - P. A. N. S. Anuradha; T. Udayangani; G. S. Jayarathna (Colombo Business Journal)
This study explores how financial behaviour mediates the relationship between financial planning, self-control and retirement well-being among employees in Sri Lanka. Using quantitative methods and a cross-sectional research design, data was gathered from 672 employees across various sectors. The findings indicate a partial mediation of financial behaviour on financial planning and self-control on retirement well-being and a significant relationship between the two variables on retirement well-being. Individuals who engage in effective financial planning are more likely to exhibit positive financial behaviour, leading to better retirement well-being. Results highlight the critical role that financial behaviour plays in determining retirement well-being, with efficient financial planning having a greater impact than self-control. Findings provide valuable insights for individuals, policymakers, and researchers, facilitating informed decision-making regarding retirement well-being. Further, it contributes to the literature by introducing financial planning as having a significant impact on retirement well-being through financial behaviour in the context of a developing country.